Lymphatic interventions for isolated, iatrogenic chylous ascites: A multi-institution experience - Majdalany, Bill S.; Khayat, Mamdouh; Downing, Trevor; Killoran, Timothy P.; El-Haddad, Ghassan; Khaja, Minhaj S.; Saad, Wael A. (European journal of radiology, 2018)
•Lymphangiography and lymphatic embolization is safe and effective for the treatment of iatrogenic chylous ascites.•Greater than 90% of patients whose leak was visualized had resolution of chylous ascites.•Combining different technical approaches, and if necessary repeat intervention, improves clinical success. Lymphangiography and thoracic duct embolization are established treatments for post-surgical chylothorax. There is only limited experience in their application to treat post-surgical chylous ascites. A multi-center analysis of the technical and clinical success of lymphangiography and lymphatic interventions in the treatment of isolated, iatrogenic chylous ascites is reported. 21 patients (14 males; 7 females) aged 3–84 years (mean 56.9 years; median 63 years) were treated for isolated, iatrogenic chylous ascites between August 2012 and January 2018. Initial referrals occurred between 5–330 days (mean 72.7 days; median 40 days) after failing conservative therapy. Daily leak volumes ranged from 100 to 3000 mL. Lymphangiographic findings, techniques, clinical outcomes, and complications were recorded. 21 patients underwent 29 procedures. Seven patients underwent multiple procedures after chylous ascites persisted. Bilateral nodal lymphangiography (NL) was technically successful in all (100%) patients. Lymphangiography identified a leak in 14/21 (67%) patients and in 16/29 procedures (55%). Ten procedures (34%) consisted of NL alone and one (3.4%) consisted of NL combined with lymphatic disruption (LD). Six procedures (21%) consisted of nodal glue embolization (NGE) while nine procedures (31%) were catheter-based lymphatic embolization. Three separate patients underwent three procedures (10%) consisting of balloon-occluded retrograde abdominal lymphatic embolization. Clinical success, defined as no additional drainage of chylous ascites at 15 days, was ultimately achieved in 18/21 patients (86%). There were no major or minor complications. Lymphatic interventions can successfully treat post-surgical chylous ascites. Given the low risk of procedural complication, early intervention is encouraged.